Empowering Communities to Prevent Stunting: A Study in Sitiris-Tiris Village, Tapanuli Tengah Regency, North Sumatra Province - Gaja, Fatma Zuhro; Sahrul, Sahrul (TEMALI : Jurnal Pembangunan Sosial, 2024)
Stunting in children, caused by chronic malnutrition from ages 0-5, negatively impacts physical and psychomotor development as well as their future. This nutritional deficiency often results from a lack of public knowledge about stunting and preventive measures. This study aims to explore community empowerment efforts to prevent stunting in Sitiris-tiris Village, Andam Dewi District, Tapanuli Tengah Regency, North Sumatra Province. The research employs a qualitative method. Data collection involves direct observation at Posyandu Beringin in Sitiris-tiris Village and interviews with 10 informants, including midwives, nutritionists, cadres, and mothers of young children. The findings reveal that community empowerment through two main programs—educational outreach and DASHAT (Healthy Kitchen to Overcome Stunting)—successfully reduced the stunting rate in the village. The educational outreach program increased parents' knowledge about stunting, while DASHAT focused on improving healthy eating patterns as a preventive measure against stunting. The reduction in stunting rates reflects the success of the community empowerment efforts in the village.